The Status of Metabolic Control in Patients With Type 2 Diabetes Attending Dasman Diabetes Institute, Kuwait - Qaddoumi, Mohammad; Al-Khamis, Yousuf; Channanath, Arshad; Tuomilehto, Jaakko; Badawi, Dalia (Frontiers in Endocrinology, 2019)
Purpose: To evaluate metabolic control in patients with type 2 diabetes at Dasman Diabetes Institute (DDI, Kuwait), a specialist diabetes clinic and research center, and to investigate its association with patient demographics and clinical characteristics. Methods: Data from 963 patients with type 2 diabetes were retrospectively collected from the Knowledge Based Health Records maintained at DDI for patients who attended DDI during 2011–2014. The collected data included patient demographics, clinical characteristics, and anti-diabetic medications. Student's t-test was used to evaluate the differences in mean values between poor and good glycemic control groups. Categorical variables were assessed using chi-square analysis with Fisher's exact test for small data sets. Results: The patients' mean age was 53.0 ± 9.5 years with equal number of males and females. Females (34.4 ± 7.2 kg/m2) had a higher mean body mass index than males (32.1 ± 6.4 kg/m2). The mean fasting blood glucose and HbA1c levels were 9.6 ± 3.8 mmol/L and 8.5 ± 1.8%, respectively. Dyslipidemia (46%) and hypertension (40%) were the most common comorbidities, whereas nephropathy (36%) and neuropathy (35%) were the most common diabetic complications. The most commonly used anti-diabetic medication was metformin (55%). Factors significantly associated with poor glycemic control (HbA1c level ≥ 7%) included insulin use; neuropathy or foot ulcers as diabetic complications; and elevated systolic blood pressure and total cholesterol, low-density lipoprotein (LDL) cholesterol, triglycerides, and fasting blood glucose levels. Factors significantly associated with good glycemic control included metformin use and elevated high-density lipoprotein cholesterol level. The proportion of patients with good glycemic control (HbA1c level < 7%) was 29.5%. A large proportion of the patients with poor glycemic control were only administered monotherapy drugs, and two-thirds of the patients were obese. Further, the American Diabetes Association (ADA) recommendations for blood pressure and LDL cholesterol level were met (62 and 63%, respectively) by follow-up year 4. Conclusion: The therapeutic management of type 2 diabetes in Kuwait is suboptimal. Therapeutic strategies should ensure better adherence to ADA guidelines, evaluate the high obesity rates, and adherence to lifestyle recommendations by patients, and continually promote diabetes education and self-empowerment.